Scratch Card Transactions with Prizes from an Islamic Legal Perspective: A Study in Dekatagung Village, Gresik - Nuruz Zakiyah; Ainun Barakah; Hanief, Azril (Universitas Islam Negeri Raden Intan Lampung, 2025)
The phenomenon of buying and selling prize scratch cards, which is rampant in Dekatagung Village, Sangkapura District, Gresik Regency, has attracted public attention because it offers entertainment and the opportunity for prizes. However, it raises issues when examined from an Islamic legal perspective. Therefore, the focus of this article is on the validity of prize scratch card transactions from an Islamic legal perspective. The purpose of this article is to analyze the validity of prize scratch card transactions from an Islamic legal perspective in Dekatagung Village, Sangkapura District, Gresik Regency. The research used field research, qualitative methods with a descriptive approach, and data collection techniques through interviews and direct observation in the field. The results indicate that these transactions contain elements of uncertainty and gambling, which are prohibited in Islam. This practice also has a negative impact on the socio-economic aspects of the community. This research is the first field study in Dekatagung Village to specifically examine this practice from an Islamic legal perspective. The implications of this research demonstrate the importance of Islamic economic education and supervision of similar buying and selling practices in the community. This research contributes to the preparation of local fatwas regarding transactions containing elements of gharar and maysir, particularly in the context of local culture.